A 5-year longitudinal evaluation in patients with mild cognitive impairment by 11C-PIB PET/CT: a visual analysis. Issue 5 (May 2019) - Jiménez-Bonilla, Julio F.; Quirce, Remedios; De Arcocha-Torres, María; Martínez-Rodríguez, Isabel; Martínez-Amador, Néstor; Sánchez-Salmón, Aida; De la Fuente-Gómez, Francisco; Rodríguez, Eloy; Sánchez-Juan, Pascual; Banzo, Ignacio
Abstract : Objective: The aim of this study was to evaluate the cerebral amyloid distribution in patients with mild cognitive impairment (MCI), assessed by carbon-11-Pittsburgh compound B ( 11 C-PIB) PET/CT, after 5 years of follow-up. Patients and methods: Ten amnestic MCI (A-MCI) and four nonamnestic (NA-MCI) patients were studied by 11 C-PIB PET/CT and re-evaluated 5 years later by a new 11 C-PIB PET/CT. PET/CT scans were acquired 60–90 min after the administration of 555 MBq 11 C-PIB and analyzed visually, to obtain a score of the cerebral cortical 11 C-PIB retention in the frontal, basal ganglia (BG), temporoparietal (TP), occipital, posterior cingulate, and cerebellum areas. Initial and 5-year follow-up 11 C-PIB retentions were compared. Results: Initially, 9/10 A-MCI patients were 11 C-PIB positive and one was 11 C-PIB negative. All four NA-MCI patients were 11 C-PIB negative. Of the 11 C-PIB-positive A-MCI patients, seven progressed to Alzheimer's disease dementia (AD-D), one to mixed dementia and one remained as A-MCI. The 11 C-PIB-negative A-MCI patient remained as A-MCI. Of the four 11 C-PIB-negative NA-MCI, one progressed to semantic dementia. All changes in 11 C-PIB retention were of low intensity. The A-MCI patients who progressed to AD-D ( n =7) showed an increase in 11 C-PIB retention in the frontal (5/7), BG (3/7), TP (3/7), occipital (1/7), and posterior cingulate (1/7) regions. The A-MCI patient who progressed to mix dementia showed an increase in 11 C-PIB retention in the frontal region. The 11 C-PIB-positive A-MCI patient who remained as A-MCI showed an increase in 11 C-PIB retention in the frontal, BG, and TP areas. The amyloid deposition in the anterior part of the brain (frontal, TP, and BG) increased more than that in the posterior part (occipital and precuneus) (7/9 vs. 2/9; P <0.05). Conclusion: PIB retention increased predominantly in the frontal, BG, and TP areas. 11 C-PIB-positive A-MCI patients mostly progressed to AD-D, showing similar topographic changes in their cerebral 11 C-PIB pattern than the patient who remained as A-MCI.